Economic vulnerabilities and trade dependencies: an analysis of key industries in Mexico-USA bilateral trade - Hernandez Urbano, Eduardo (2025)
Fil: Hernandez Urbano, Eduardo. Universidad Nacional del Litoral. Facultad de Ciencias Económicas; Argentina.